2021
DOI: 10.1186/s12913-021-06639-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of care tasks for the use of wearable transfer support robots – an observational study at nursing facilities using robots on a daily basis

Abstract: Background To reduce the physical burden of caregivers, wearable transfer support robots are highly desirable. Although these robots are reportedly effective for specific tasks in experimental environments, there is little information about their effectiveness at nursing care facilities. The aim of this study was to identify care tasks and operations suitable for the use of these robots among caregivers in nursing facilities where these robots have been in use on a daily basis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…It should be noted that our study was conducted in a nursing home that accommodated residents who need assistive devices such as wheelchairs to move around and might need assistance to transfer to a wheelchair. Thus, there is a need for transfer assistance to ensure residents can access their life spaces, and, naturally, such access is heavily dependent on the availability of the caregivers, as well as other institutional factors [ 8 , 13 , 17 ], including care routines (timing and place of meals, timing and number of transfers) [ 13 ] and the scheduling of regular events [ 13 , 17 ]. Other factors may include the constraints imposed by working environments in which caregivers ordinarily need to carry out a wide variety of care tasks with limited manpower, including direct care such as transferring, toileting, and mealtime and bathing assistance, as well as the documentation and administration of medication [ 8 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that our study was conducted in a nursing home that accommodated residents who need assistive devices such as wheelchairs to move around and might need assistance to transfer to a wheelchair. Thus, there is a need for transfer assistance to ensure residents can access their life spaces, and, naturally, such access is heavily dependent on the availability of the caregivers, as well as other institutional factors [ 8 , 13 , 17 ], including care routines (timing and place of meals, timing and number of transfers) [ 13 ] and the scheduling of regular events [ 13 , 17 ]. Other factors may include the constraints imposed by working environments in which caregivers ordinarily need to carry out a wide variety of care tasks with limited manpower, including direct care such as transferring, toileting, and mealtime and bathing assistance, as well as the documentation and administration of medication [ 8 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need for transfer assistance to ensure residents can access their life spaces, and, naturally, such access is heavily dependent on the availability of the caregivers, as well as other institutional factors [ 8 , 13 , 17 ], including care routines (timing and place of meals, timing and number of transfers) [ 13 ] and the scheduling of regular events [ 13 , 17 ]. Other factors may include the constraints imposed by working environments in which caregivers ordinarily need to carry out a wide variety of care tasks with limited manpower, including direct care such as transferring, toileting, and mealtime and bathing assistance, as well as the documentation and administration of medication [ 8 , 31 , 32 ]. Considering these limitations, any reduction in the need for multiple caregivers for transfers as a result of using Resyone devices should contribute to an improvement in the operational efficiency of transfer assistance [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time study was similar to an observational study that was reported previously as a time-motion study [15], in which all caregivers were observed directly. In brief, a professional observer, following a caregiver throughout the daytime shift, analyzed the tasks and recorded them using codes that were based on the code chart used in the Ministry of Health, Labour, and Welfare, Survey of Long-term Care in Japan [16], which has been translated into English and is available as supplementary materials in our previous study of the pro ciency of exoskeleton usage in nursing care facilities [17]. Note that in the present study, care code 222: Transfer was subdivided into 22201: Verbal action for transfer, 22202: Actual assistance, and 22203: Watching after transfer in order to examine the transfer situations in more detail.…”
Section: Observation Protocolmentioning
confidence: 99%
“…Time–motion studies are widely used in fields such as industrial engineering to measure the amount of time and movements that employees require to complete work tasks ( Burri Jr. & Helander, 1991 ; Magu et al, 2015 ). Time–motion studies are increasingly used in health care settings to assess and improve clinic workflow ( Kato et al, 2021 ; Solomon et al, 2021 ). Examples include comparing nurses’ time spent in face-to-face versus care management activities in the Collaborative Chronic Care Model (CCM) ( Glick et al, 2004 ), comparing physicians’ time spent working in the electronic health record versus face-to-face time with patients in clinic visits ( Young et al, 2018 ), and improving patient wait times by assessing and restructuring clinical practice patterns to eliminate inefficiencies ( Racine & Davidson, 2002 ).…”
mentioning
confidence: 99%